2021
DOI: 10.3390/ijms22168572
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Drugs for the Treatment of B Cell Malignancies

Abstract: Accumulating evidence suggests that the tumor microenvironment (TME) is involved in disease progression and drug resistance in B cell malignancies, by supporting tumor growth and facilitating the ability of malignant cells to avoid immune recognition. Immunomodulatory drugs (IMiDs) such as lenalidomide have some direct anti-tumor activity, but critically also target various cellular compartments of the TME including T cells, NK cells, and stromal cells, which interfere with pro-tumor signaling while activating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 166 publications
(206 reference statements)
0
28
0
Order By: Relevance
“…The first antibody approved for therapy that utilizes CDC, as part of its therapeutic mechanism, was rituximab (anti-CD20). This antibody is approved for relapsed indolent Non-Hodgkin lymphomas (NHL) and its newer iteration, rituximab with hyaluronidase for subcutaneous injection, was more recently approved for refractory follicular lymphoma, diffuse large B-cell lymphoma (DLBCL), and chronic lymphocytic leukaemia (CLL) ( 54 ). Other CD20 antibodies such as ofatumumab and ibritumomab ( 55 ), and anti-CD52 (alemtuzumab) were also showed to have complement activating properties and lyse cancer cells through CDC ( 56 ).…”
Section: Complement Dependent Cytotoxicity As Mechanism In Anti-cance...mentioning
confidence: 99%
“…The first antibody approved for therapy that utilizes CDC, as part of its therapeutic mechanism, was rituximab (anti-CD20). This antibody is approved for relapsed indolent Non-Hodgkin lymphomas (NHL) and its newer iteration, rituximab with hyaluronidase for subcutaneous injection, was more recently approved for refractory follicular lymphoma, diffuse large B-cell lymphoma (DLBCL), and chronic lymphocytic leukaemia (CLL) ( 54 ). Other CD20 antibodies such as ofatumumab and ibritumomab ( 55 ), and anti-CD52 (alemtuzumab) were also showed to have complement activating properties and lyse cancer cells through CDC ( 56 ).…”
Section: Complement Dependent Cytotoxicity As Mechanism In Anti-cance...mentioning
confidence: 99%
“…When bound to CRBN, IMiDs recruit new substrates, such as Ikaros/Aiolos and CK1ɑ, to the complex, thus mediating their ubiquitination and subsequent degradation. 110 Nicolas H. Thomä from the Friedrich Miescher Institute discussed how small molecule IMiDs serve as molecular glues to target novel substrates to the E3 ligase for ubiquitination and degradation. The structure of CRBN bound to lenalidomide and CK1ɑ, solved in Thomä's group, shows that lenalidomide sits at the interface of CRBN and a βhairpin loop within CK1ɑ.…”
Section: Molecular Glues Bring New Substrates For E3 Ubiquitin Ligasesmentioning
confidence: 99%
“…The primary target of IMiDs is CRBN, a substrate receptor of the CUL4 CRL. When bound to CRBN, IMiDs recruit new substrates, such as Ikaros/Aiolos and CK1ɑ, to the complex, thus mediating their ubiquitination and subsequent degradation 110 …”
Section: Targeting Protein Degradation Pathways For Cancer Therapiesmentioning
confidence: 99%
“…Indeed, it is now well shown that IMIDs target CRBN, leading to the degradation of key neo-substrates such as IKAROS and AIOLOS, but also ZMYM2 (ZNF198), a transcription factor involved in balanced chromosomal rearrangements with FGFR1 and FLT3 [66]. Given its action via CRBN, lenalidomide has a direct cytotoxic effect against neoplastic cells, but also a strong impact on the peripheral immune system as well as the TME by immunomodulating and fostering the activity of T and NK and downregulating Treg and myeloid-associated tumor cells, such as M2 macrophages [67][68][69][70][71][72][73]. Furthermore, in preclinical models of non-Hodgkin lymphoma (NHL), lenalidomide enhanced the ADCC of rituximab, which was the rationale of the combination of the two drugs in NHL [71,74].…”
Section: Rationale Of Imids In MCL and Potential Mechanism Of Actionmentioning
confidence: 99%